Quercus infectoria gall loaded patches for wound dressing: A comparison of fabrication methods - Aydin, Sema Tugce; Demirhan, Ilter; Sengor, Mustafa (ELSEVIER GMBH, 2022)
Introduction: Increasing antibiotic resistance leads wound care specialists to promote chronic wound healing with plant-based sources. The aim of this study is to extract Quercus infectoria gall and to investigate the performance of the extracted QIG wound dressings produced by three different fabrication techniques.Methods: The effect of the (i) electrospinning, (ii) 3D printing, (iii) hydrogel casting techniques on the properties of the wound dressings was exhibited. Morphological, physical, and chemical properties and differences of the resulting samples were established using Fourier transform infrared spectroscopy, scanning electron microscopy, mechanical and differential scanning calorimetry tests. Antimicrobial Susceptibility Testing for two organisms (Escherichia coli and Staphylococcus aureus) and UV spectroscopy tests were performed.Results: Results revealed that fabrication techniques have effects on the dressings by means of surface chemical compositions and mechanical performances. Also, release kinetics and X-ray diffraction analysis of QIG were established for the first time in the literature. Discussion/conclusion: Antibacterial tests were for one strain for each group and for both gram negative and positive organisms. The highest area of the antibacterial effect belongs to the electrospinning case which has 12 mm diameter on gram-positive bacteria thanks to the potassium-rich surface chemistry of the fibers revealed via energy dispersive X-ray analysis. These findings will lead to patches that can prevent over usage of antibiotics.
Keywords: 3D printing; Quercus infectoria gall; Wound dressing; Film; Biopolymers; DRUG-DELIVERY; COMPOSITE; CHITOSAN; BEHAVIOR; ALCOHOL; TISSUE; Integrative & Complementary Medicine